INFLUENCE OF THE USA AND CHINA ON THE TRANSFORMATION OF THE WORLD OIL MARKET - A. Zh. Panzabekova; An Ha Nguen; A. Sh. Suleimenova (Экономика: стратегия и практика, 2019)
This article considers the state of the oil market of the United States and China, as dominant countries on which the development of the world as a whole depends, as well as countries that have been significantly affected by the transformational processes of the oil market. For example, the US shale revolution caused serious imbalances for the world oil market, which led to a sharp decline in oil prices, but made the United States one of the world’s leaders in oil production, and China the world leader in oil import. In this regard, the article analyses the world oil market, namely,the potential and prospects of the oil market of the United States and China, and their impact on the transformation of the world oil market. Given that the dynamic of the oil market is constantly changing, and prices per barrel of oil are constantly fluctuating, the change in the energy policy of the leading oil powers, can significantly affect further growth and development not only for developing oil markets such as Kazakhstan, but also for the global market as a whole.